Guide plane retention in removable partial dentures - Mothopi, Matshediso M (My University, 2011)
Purpose: The purpose of this study was to measure and compare the influence of abutment teeth guide planes and partial denture guiding surfaces on the retention of removable partial dentures. Method: An upper typodont model was modified by removing both second premolars and first molars, thus creating two bounded saddles. An impression of the model was made with irreversible hydrocolloid and a cast poured, on which an acrylic resin based removable partial denture (RPD) was made. To this denture a hooking device was added so that the model and denture could be placed on a custom-made platform and jig on a universal testing machine (Instron, UK). The RPD was then removed from the model along its path of insertion (perpendicular to the occlusal plane) as well as at 2° and 5° and the maximum load recorded. The typodont model was then modified by making guide planes on the abutment teeth, and a second RPD made and the procedure repeated. This RPD was then modified by creating guiding surfaces directly against the guide planes using autopolymerising resin, and the procedure again repeated. Each measurement was made 10 times at each path of insertion/withdrawal, resulting in 90 measurements. Results There were some differences between the different paths of withdrawal in each of the three situations, explicable by the lack of ideal contact in the first two dentures, and the much improved contact in the third, which caused the teeth in the model to move on withdrawal. Overall,there were significant differences between the three models. There 5 was a significant increase in retentive force of 1.6 times from denture 1 to denture 2, of 7.6 times from denture 2 to denture 3, and 12.3 times from denture 1 to denture 3. Conclusion This study confirmed that guide planes increase the retention of an RPD, but that when guiding surfaces of the denture are adapted closely to the guide planes on the teeth, there is a considerable increase in retention
A research report submitted for partial completion of Masters in Dentistry in Prosthodontics
Keywords: Denture, Partial